ASSESMENT OF THE DEVELOPMENT OF SPEED BEHIND SPEED RADAR SIGN ON THE STREET ŽELATOVSKÁ IN PŘEROV (Perner's Contacts, 2012)
This paper deals with find out, how drivers are reacting on radar speed sign in terms of speed changes. Measurements were carried out on the stationary radar speed sign. This device is installed on the street Želatovská in Přerov.
Keywords: Radar speed sign, speed measurement, safety of transport